The Complexity of the Caspian Basin - Markella, Koutsouradi; John, Karkazis; Petros, Siousiouras; Dionysia, Chondrogianni (European Scientific Journal, ESJ, 2018)
The collapse of the Soviet Union and the emergence of newly independent States marked the uprising of a new era in the region of the Caspian Basin. Failing to reach a consensus regarding the legal nature of the Caspian, Russia, Turkmenistan, Iran, Azerbaijan, and Kazakhstan’s policies have been characterized by a perpetual pursuit of establishing themselves as key-role agents in the region. The question about “Lake or Sea” is yet to be answered after many decades. This paper focuses on analyzing the significance of the Caspian Basin for the littoral States and how it determines their political agenda.